Regression of Peyer's patches in Gαi2 deficient mice prior to colitis is associated with reduced expression of Bcl-2 and increased apoptosis. Issue 3 (1st September 2002) - Öhman, L; Franzén, L; Rudolph, U; Birnbaumer, L; Hörnquist, E Hultgren
Abstract : Background: G protein deficient (Gαi2−/−) mice spontaneously develop an inflammatory bowel disease (IBD) closely resembling ulcerative colitis. Previous studies have demonstrated that gut T cells are hyperreactive to the endogenous microflora in most IBD models. Aims: The aim of this study was to analyse Peyer's patches (PP), the inductive sites for gut mucosal immune responses. Subjects and methods: Gαi2−/− mice, an animal model for IBD, were analysed using immunological methods with regard to phenotype and function. Results: We found significantly decreased numbers of PP in Gαi2−/− mice. Even before the onset of colitis, Gαi2 deficient animals exhibited diminished size of PP, as judged by histology. This involution of PP was associated with strongly increased levels of apoptotic lymphocytes, associated with decreased levels of antiapoptotic intracellular protein Bcl-2. PP T lymphocytes showed highly elevated production of interferon γ in response to the enteric flora compared with PP T cells from wild-type mice, which produced predominantly interleukin 10. Conclusions: Thus even before the onset of colitis, the PP in Gαi2 deficient mice is a Th1 dominated milieu associated with downregulated levels of Bcl-2, resulting in increased apoptosis of lymphocytes leading to regression of PP. We speculate that this Th1 dominated microenvironment in the inductive site for mucosal immune responses contributes to the development of colitis in Gαi2 deficient mice.